An Unusual Acceleration of Amination Reactivity by the Proximal Ester Groups in Catechol Diesters: An Efficient Way for Peptide Synthesis - Wu, An; Ikeda, Hirotaka; Yamamoto, Hisashi (Precision Chemistry, 2023)
Peptide bond formation has drawn more and more attention due to its importance in medicinal chemistry and drug discovery. Using active esters to construct peptide bonds is an indispensable strategy in this field. We herein report a fast and efficient amination reaction to synthesize peptides from catechol diesters. Catechol monoesters are good active esters in peptide synthesis due to the anchimeric assistance effect. In previously reported work, the amination reaction was inactivated if the 2-hydroxyl group in the catechol esters was functionalized. However, we found an unusual acceleration of the amination reactivity when the 2-hydroxyl group was functionalized as an ester group. The reaction can be complete in 2–3 min in some cases. This acceleration was found through experimental studies to not result from the anchimeric assistance effect. We proposed a π*−π* interaction pathway between the two proximal ester groups. Some computational studies were made to support this assumption.